2002
DOI: 10.1021/jm0255116
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Nonsteroidal Liver X Receptor Agonist through Parallel Array Synthesis of Tertiary Amines

Abstract: A potent, selective, orally active LXR agonist was identified from focused libraries of tertiary amines. GW3965 (12) recruits the steroid receptor coactivator 1 to human LXRalpha in a cell-free ligand-sensing assay with an EC(50) of 125 nM and profiles as a full agonist on hLXRalpha and hLXRbeta in cell-based reporter gene assays with EC(50)'s of 190 and 30 nM, respectively. After oral dosing at 10 mg/kg to C57BL/6 mice, 12 increased expression of the reverse cholesterol transporter ABCA1 in the small intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
261
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(268 citation statements)
references
References 23 publications
6
261
0
1
Order By: Relevance
“…Surprisingly, expression of Leptin gene was 2.5-fold higher in SC fat of LXRα −/− mice compared with WT mice, whereas no differences were observed between groups in gonadal fat. Recent reports have shown that ectopic Ucp1 expression in WAT (24) can appear because of differentiation of white fat cells into brown fat cells in the WAT (4,25). A 10-fold increase associated with a fivefold decrease of Ucp1 expression was observed in gonadal vs. SC fat, respectively, in LXRα −/− mice compared with WT mice ( Fig.…”
Section: Increased Subcutaneous Leptin Expression and Gonadal Fat Ucp1mentioning
confidence: 81%
“…Surprisingly, expression of Leptin gene was 2.5-fold higher in SC fat of LXRα −/− mice compared with WT mice, whereas no differences were observed between groups in gonadal fat. Recent reports have shown that ectopic Ucp1 expression in WAT (24) can appear because of differentiation of white fat cells into brown fat cells in the WAT (4,25). A 10-fold increase associated with a fivefold decrease of Ucp1 expression was observed in gonadal vs. SC fat, respectively, in LXRα −/− mice compared with WT mice ( Fig.…”
Section: Increased Subcutaneous Leptin Expression and Gonadal Fat Ucp1mentioning
confidence: 81%
“…An initial screening of possible ligands for these receptors revealed that T-0901317 and GW3965 (see Fig. 1 for chemical structures), both previously reported as agonists of mammalian LXRs [23,24], also robustly activated the two Xenopus LXRs, as well as the zfLXR. T-0901317 was selected as the reference 'maximal' activator for the vertebrate LXRs in this study; the maximal activation of all other tested compounds at these receptors was then compared to T-0901317.…”
Section: Ligand Specificity Of Vertebrate Lxrsmentioning
confidence: 99%
“…In mammals, GW3965 has been reported as a selective ligand for LXRs relative to other NRs (although it does not distinguish between LXRα and LXRβ) [23]. We also tested GW3965 on Xenopus laevis and zebrafish FXRs, vitamin D receptors (VDRs, NR1I1), and pregnane X receptors (PXRs, NR1I2) and found no effect of this compound on these receptors; in contrast, T-0901317 activated the zebrafish FXR in the low micromolar range (E.J.…”
Section: Ligand Specificity Of Vertebrate Lxrsmentioning
confidence: 99%
“…Next we evaluated whether pharmacological activation of LXRs using synthetic ligands could prevent matrix degradation in human cartilage. A highly selective LXR ligand, GW3965 (18), which has been broadly used in the LXR research field, was chosen for this study. An ex vivo articular cartilage explant model that allows investigation of the direct effects of proinflammatory cytokines such as IL-1β and OSM on cartilage was used.…”
Section: Deletion Of Lxrβ Gene In Mice Increases Cartilage Matrix Catmentioning
confidence: 99%